The Market for Remittance Services in the Czech Republic : Outcomes of a Survey among Migrants - Nicolì, Marco; Corazza, Carlo (World Bank, 2012)
This survey was conducted by the World Bank Payment Systems Development Group, at the request of the Ministry of Finance of the Czech Republic, as a follow up to the World Bank-led mission that visited the country in 2008 to assess the market for remittances. This survey aims at analyzing the main characteristics of the market for remittances in the Czech Republic and should serve as a guide for both public authorities and the private sector in identifying possible actions to improve the efficiency of the market. A total of 880 migrants from eight different nationalities were interviewed during the summer of 2009 in Prague. The nationalities selected represent the largest and most important migrant communities in the country: China, Moldova, Mongolia, Poland, the Russian Federation, the Slovak Republic, Ukraine, and Vietnam. The following main findings can be extracted from the analysis of the survey's outcomes: i) a low level of transparency and consumer protection can be observed in the market for remittances in the Czech Republic. Senders are often not provided with all the relevant information by the Remittance Service Provider (RSP) at the moment of the transaction; ii) the lack of transparency is confirmed by the analysis of the cost as perceived by the interviewees, who do not generally consider the margin applied by the RSP as a price component. As a result, remittance senders are in general not aware of the actual cost that they are paying for the service; and iii) the market is dominated by Money Transfer Operators (MTOs) and, in particular, some MTOs hold the great majority of the market shares.